Contrast Staining on CT after DSA in Ischemic Stroke Patients Progresses to Infarction and Rarely Hemorrhages - Amans, Matthew R. (Centauro S.r.l., 2014)
Contrast staining of brain parenchyma identified on non-contrast CT performed after DSA in patients with acute ischemic stroke (AIS) is an incompletely understood imaging finding. We hypothesize contrast staining to be an indicator of brain injury and suspect the fate of involved parenchyma to be cerebral infarction. Seventeen years of AIS data were retrospectively analyzed for contrast staining. Charts were reviewed and outcomes of the stained parenchyma were identified on subsequent CT and MRI. Thirty-six of 67 patients meeting inclusion criteria (53.7%) had contrast staining on CT obtained within 72 hours after DSA. Brain parenchyma with contrast staining in patients with AIS most often evolved into cerebral infarction (81%). Hemorrhagic transformation was less likely in cases with staining compared with hemorrhagic transformation in the cohort that did not have contrast staining of the parenchyma on post DSA CT (6% versus 25%, respectively, OR 0.17, 95% CI 0.017 – 0.98, p = 0.02). Brain parenchyma with contrast staining on CT after DSA in AIS patients was likely to infarct and unlikely to hemorrhage.